Management of broken rotary file in root canal by using bypass technique: Case report - Younesi, Taravat; Alexandrovich, Volodko A.; Younesijadidi, Amirhossein (Hasanuddin University, 2025)
AbstractObjective: In this report it was described the clinical and radiographic outcomes of fracture of a #S1 rotary NiTi file in MB canal of tooth 4.6, at the middle of canal in a 35 year-old female patient. One of the effectual techniques for managing broken instruments is the instrument bypass technique, which is conservative, simple and less invasive for instrument fragment removal.Methods: Conservative treatment was performed, involves proper biochemical preparation followed by placement of calcium hydroxide during first visit and on the second visit bypassing fractured fragment in canal with K-files and rotary NiTi files. Also irrigation was done with 3% NaOCl, ethylenediaminetetraacetic acid (EDTA) and 2% Chlorohexidine (2% CHX), sterile distilled water after changing of irrigation solution type. Periapical X-ray investigations were used to observe radiographic success of this treatment.Results: In these case, the fractured fragment was successfully bypassed and there was no apical plunging of the separated instrument. The whole treatment was accomplished with minimal damage to the surrounding dentin of the tooth and supporting tissues.Conclusion: As removal of a fractured file is associated with considerable risk, bypassing the fragment should be also considered. Fractured instrument management with a bypass approach is a favorable possible option over ultrasonic retrieval, surgical endodontic, chemical and surgical treatment.